The design and implementation of rain sensitive triggering system for windshield wiper motor - (:unkn) unknown (My University, 2001)
Automotive windshield wiper systems have three main components, which are wiper arms, connection mechanism and an electric motor that drives this mechanism. A windshield wiper motor must be operated when rainsqualls obscure the driver's sight area. Currently, windshield wiper motor systems are controlled in two different ways: in the first, the driving of motor is realized with predetermined constant time intervals using time relays. Secondly, the wiper motor system can also be controlled by the principle based on the infrared light reflection from the windshield. In this work, a new system is designed to drive a wiper motor using sensors that detect the wetness and rainsquall concentration on the windshield. The sensors are located on the windshield and are operated based on the feature of the rainsquall's weak electric conductivity. The system structure can be designed as controllable by single or multiple sensors. The experimental results based on a single sensor show the reliability of the system. © 2001 IEEE.